Pupillometric assessment of excessive daytime sleepiness in narcolepsy-cataplexy. - Newman, Janice. (University of Ottawa (Canada), 1991)
Ten untreated patients with narcolepsy-cataplexy and ten age and sex matched normals between the ages of 20 and 71 underwent pupillometric analyses immediately prior to each of five Multiple Sleep Latency Test (MSLT) sessions. Although narcoleptics were sleepier in terms of both their Stanford Sleepiness Scale (SSS) ratings and their latencies to sleep onset, the baseline pupil diameter, pupillary light reflex and pupillary orienting response did not differentiate between groups. Narcoleptics did, however, exhibit a significantly greater frequency of spontaneous oscillations in the dark-adapted state than did controls. These findings indicate that pupillary stability may serve as a supplementary diagnostic tool for narcolepsy-cataplexy. The results are discussed with the view that psychosensory restoration of alertness, among other extraneous variables, must be controlled for when utilizing pupillometric techniques. A review of the literature indicates a variety of methodological and statistical shortcomings that must be amended. Suggestions are made for improving the reliability and validity of the pupillometric approach.
Keywords: Psychology, Experimental.